Odpowiedzi

2010-01-12T17:52:38+01:00
36-2+24+5+48=111
6-2+10+20-6=28
5+16-15-18+40-5=23
3(1-8+2+4-12+2)=3-24+6+12-36+6=-33
1 5 1
2010-01-12T18:12:42+01:00
3x - 2 - 2x + 5 + 4x = 3 *12 -2 -2 *12 +5 +4 *12 = 36 -2 -14 +5 +48 = 34 -14 +53 = 34 +39 = 73

3a - b + 5a+ 2b - 6 = 3 *2 -2 +5 *2 +2 *2 -6 = 6 -2 +10 +4 -6 = 6 -8 +14 = 12

x + 2y - 3 y - 3z + 5z - x = 5 +2 *8 -3 *8 -3 *6 +5 *6 -5 = 5 +16 + 24 +24 +30 -6 = 21 +24 +54 = 45 +54 = 99

3 ( x - 4z + y + 4x - z +2y) = 3 *(1 -4 *12 +2 +4 *1 - 12 +2 *2 = 3 *( 1+ 48 +2 +4 -12 +4) = 3 *( 55 -8) = 3 *47 = 141


nie wiem czy to jest dobrze:/